Kecerdasan Emosional, Prestasi Belajar, Gaya Materi - Nada, Nada; Mustapa, Hisbullah; Harahap, Nur Kholija; Oktavia, Sri Wina (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
This research is one of the first studies to explore the level of emotional intelligence and level of learning achievement of class VIII students on style material in Indonesia. The research method used is quantitative research. The population in this study consisted of all students in class VIII of Junior high school 16 Jambi City and Junior high school Izzuddin Shah. The sampling technique used was random sampling. The research instrument used was a statement questionnaire given to students. The data analysis used was descriptive statistics. The results of research on students’ emotional intelligence showed that they were in the good category with a percentage of 42% at Junior high school 16 Jambi City and in the good category with a percentage of 52% at Junior high school Izzuddin Shah. The findings provide new insights and implications for enhancing the emotional intelligence and learning achievement of students, especially on style material, in the Indonesian context.